System dynamics an introduction - Rowell, Derek (Prentice Hall, 1997)
Rowell and Wormley use a linear graph approach. This contrasts with the bond graph approach or no graph approach. This is the first modern linear graph System Dynamics that has been published in 30 years. Chapters are organized so that introductory material is presented first, with more advanced topics coming later. Contains exceptionally clear presentation of Frequency response. Features detailed development of the construction of lumped-parameter system models from sets of primitive elements; and modeling techniques are presented using an energy based state-space formulation method that provides linkages to classical system representations.